A poroelastic immersed finite element framework for modelling cardiac perfusion and fluid–structure interaction. (28th February 2021) - Richardson, Scott I. Heath; Gao, Hao; Cox, Jennifer; Janiczek, Rob; Griffith, Boyce E.; Berry, Colin; Luo, Xiaoyu
Abstract: Modern approaches to modelling cardiac perfusion now commonly describe the myocardium using the framework of poroelasticity. Cardiac tissue can be described as a saturated porous medium composed of the pore fluid (blood) and the skeleton (myocytes and collagen scaffold). In previous studies fluid–structure interaction in the heart has been treated in a variety of ways, but in most cases, the myocardium is assumed to be a hyperelastic fibre‐reinforced material. Conversely, models that treat the myocardium as a poroelastic material typically neglect interactions between the myocardium and intracardiac blood flow. This work presents a poroelastic immersed finite element framework to model left ventricular dynamics in a three‐phase poroelastic system composed of the pore blood fluid, the skeleton, and the chamber fluid. We benchmark our approach by examining a pair of prototypical poroelastic formations using a simple cubic geometry considered in the prior work by Chapelle et al (2010). This cubic model also enables us to compare the differences between system behaviour when using isotropic and anisotropic material models for the skeleton. With this framework, we also simulate the poroelastic dynamics of a three‐dimensional left ventricle, in which the myocardium is described by the Holzapfel–Ogden law. Results obtained using the poroelastic model are compared to those of a corresponding hyperelastic model studied previously. We find that the poroelastic LV behaves differently from the hyperelastic LV model. For example, accounting for perfusion results in a smaller diastolic chamber volume, agreeing well with the well‐known wall‐stiffening effect under perfusion reported previously. Meanwhile differences in systolic function, such as fibre strain in the basal and middle ventricle, are found to be comparatively minor. Abstract : In this work we develop a poroelastic immersed finite element framework to model left ventricular dynamics in a three‐phase poroelastic system, composed of the pore blood fluid, the skeleton, and the chamber fluid. To benchmark our approach, we examine a pair of prototypical poroelastic formations using a cubic geometry, before modelling the poroelastic dynamics of a three‐dimensional left ventricle. In all examined cases we obtain excellent agreement with previously published results and moreover show that this poroelastic LV agrees well with prior experimental studies, demonstrating features such as the wall‐stiffening effects under perfusion.